Empowering Women of Childbearing Age as Agents of Change in Early Cervical Cancer Prevention: A Community-Based Education Program in Banyuwangi - Anifah, Fulatul; Irma Maya Puspita (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
Nasyiatul 'Aisyiyah branch of Purwoharjo, Banyuwangi, as one of the autonomous organizations under Muhammadiyah, plays a significant role in community health development, particularly in disease prevention efforts. The main issue faced by the partners is the relatively low level of knowledge among community members, especially women of reproductive age (15–49 years), regarding cervical cancer and its prevention. The objective of this activity is to enhance partners' knowledge, to reduce mortality caused by cervical cancer. The implementation method of this Community Service Program (PKM) includes socialization, group discussions, and educational practices, specifically designed to encourage active understanding and participation among cadres and participants. This service activity is voluntary, so it is very important to see changes in women's attitudes or behaviors in the early detection of cervical cancer. This activity will be held on February 20-21, 2025. Indicate an increase in participants’ knowledge, with the number of respondents possessing good knowledge rising from 4 individuals (12,5%) to 26 individuals (81,25%) after the program. This demonstrates the effectiveness of group educational approaches in improving community understanding about cervical cancer and its prevention. This PKM program successfully increased the knowledge of Nasyiatul 'Aisyiyah cadres in Purwoharjo, Banyuwangi, regarding cervical cancer. Education through socialization, discussion, and practice has proven to be an effective approach to empowering community health. It can serve as a sustainable strategy to reduce the incidence and mortality rates of cervical cancer. High knowledge can change an individual's behavior to engage in activities that are beneficial to their health.